High‐grade neuroepithelial tumor with BCL6 corepressor‐alteration presenting pathological and radiological calcification: A case report. Issue 5 (13th March 2021) - Ishi, Yukitomo; Shimizu, Ai; Takakuwa, Emi; Sugiyama, Minako; Okamoto, Michinari; Motegi, Hiroaki; Hirabayashi, Shinsuke; Cho, Yuko; Iguchi, Akihiro; Manabe, Atsushi; Nobusawa, Sumihito; Tanaka, Shinya; et al.
Abstract : A 5‐year‐old girl presented with headache and vomiting. Head computed tomography and magnetic resonance imaging showed a right frontal lobe tumor with marked calcification. The patient underwent resection surgery with suspicion of anaplastic ependymoma, and the tumor was gross totally removed. Pathological examination revealed areas of dense tumor cells with a high nucleocytoplasmic ratio and myxoid areas consisting of tumor cells with a round‐shaped nucleus and eosinophilic cytoplasm. Perivascular pseudorosette, necrosis, circumscribed growth, and microcalcification were also observed. Immunohistochemistry demonstrated negative staining for glial fibrillary protein and epithelial membrane antigen. Diagnosis of a high‐grade neuroepithelial tumor (HGNET) with BCL6 corepressor ( BCOR ) alteration was made based on pathological findings and internal tandem duplication in the exon 15 of BCOR . Although calcification on radiological and pathological examination is not typical, it would be essential to recognize that calcification could appear in HGNET‐ BCOR .